Sharia Economics in Improving Community Life - Effendi, Samsul; Agustami, Eli; Sadly, Effendi (PT Inovasi Pratama Internasional, 2025)
Human resources are aknowledgeor how to organize relationships and rolesresource(workforce) owned byindividualefficiently and effectively and can be used optimally so that the goals of the company, employees and the community are achieved optimally. HR is based on a concept that every employee ismannot a machine and not merely a business resource. combining several fields of science such aspsychology,sociology, and othersHuman resource management also concernsdesign and implementation of planning systems, staffing, employee development, career management, performance evaluation, employee compensation and good labor relations. Human resource management involves all management decisions and practices that directly affect its human resources.